THE DISPUTE RESOLUTION MODEL OF VILLAGE HEAD ELECTION THROUGH NON LITIGATION - Praptianingsih, Sri; Fauziyah, Fauziyah (Tadulako Law Review, 2017)
Article Number 6 of 2014 clauses 37 verses (5) and (6) provides that the regent in the district must resolve the dispute over the election result of the village head within 30 days. At the district level, the Regional Regulations governing the settlement of village head election disputes and regulations are effective in the dispute profession.However, the laws and regulations at the local / district level have not yet clearly defined the form / format of the outcome of the dispute over the election of the village mayors. The specific purpose of this research is to formulate the model form in the effort to solve the disputes of Village mayors Election by doing syncretism of existing strategy. The Urgency of this research that is (a) need to build juridical system in handling dispute of village head election; (b) the synchronization of district regulations governing the handling of village head election disputes both vertically and horizontally (c) needs a dispute resolution strategy by developing a model of settlement that provides protection of constitutional rights and ensures that government agenda.Research activities in Jember, Bondowoso and Lumajang districts, with a total sample of 150 people. Data collection techniques use Participatory Action Research (PAR) and Focus Group Discussion (FGD) methods. The Data analysis technique using qualitative analysis.The result of this research is the policy of settlement of disputes of village head election is set forth in juridical instrument at local level, result of settlement stated in peace agreement.This Agreement is then submitted to the Court for the issuance of the Deed of Peace in order to ensure the validity of the legal force for the parties.Â